DISTRIBUŢIA ŞI ACCESUL POPUŢAŢIEI DIN REPUBLICA MOLDOVA LA SERVICIILE MEDICALE DIN PROGRAMUL UNIC AL ASIGURĂRII OBLIGATORII DE ASISTENŢĂ MEDICALĂ - Serbulenco, Aliona (Editura USM, 2024)
The topic of medical services included in the Single Program of Mandatory Medical Assistance Insurance (PU of AOAM) was and remains an important topic, addressed by politicians, civil society, but also a research topic, taking into account the multiple aspects, which meets. The conclusions and recommendations for different actors with decisionmaking power could favor the consolidation and strengthening of the capacities of the National Medical Insurance Company for a sustainable activity.